The Influence of Giving Incentives to Employee Performance in PT. Adira Dinamika Multifinance Tangerang - Isyana Emita; Dessy Suryani; Desriyani (Kusuma Negara Business School, 2020)
Incentives are one component of compensation. Providing incentives is given to motivate the workforce to improve employee performance. The purpose of this study was to determine the effect of providing incentives on employee performance at PT. Adira Dinamkia Multifinance Tangerang. The study uses quantitative descriptive analysis with methods of observation, documentation and questionnaires. The author in determining the sample using a saturated sample with the Slovin formula so that the results obtained were 37 respondents, the distribution of questionnaires using a Likert Scale. The data analysis technique uses correlation coefficient, determination coefficient, regression equation, then the authors process the data using SPSS application version 26. Based on the calculation of the correlation coefficient obtained by 0.671 where the amount of there is a strong relationship between providing incentives to employee performance at PT. Adira Dinamika Multifinance Tangerang. From the results of the calculation of the coefficient of determination can be seen that the provision of incentives affects employee performance by 45% and seen from the regression equation formed Y = 13,668 + 0.695 X this shows that there is a positive influence between giving incentives to employee performance. Then it is necessary to increase the provision of incentives to the maximum to improve employee performance.